Inflammatory Markers in Women with Polycystic Ovary Syndrome. (6th March 2020) - Rudnicka, E.; Kunicki, M.; Suchta, K.; Machura, P.; Grymowicz, M.; Smolarczyk, R.
Abstract : Several studies have reported the association between polycystic ovary syndrome (PCOS) and low-grade chronic inflammation to be of uncertain cause: obesity, insulin resistance, or PCOS itself. The aim of the study was to investigate the WBC (white blood cell) count and CRP (C-reactive protein) concentration in women with PCOS and to determine the factors that affect their concentration. The study included 200 women aged 18-40 with PCOS and 105 healthy women as the control group, recruited in the Department of Gynaecological Endocrinology of Medical University in Warsaw from 2016 to 2018. Each patient underwent clinical, biochemical, and ultrasonographic assessments. WBC and CRP were significantly higher in the PCOS group (Z = − 2, 353, p = 0, 019 and Z = − 2, 453, p = 0, 014 ). WBC positively correlated with serum insulin at 0, 60, and 120 min during the oral glucose tolerance test (INS0: r = 0, 221, p = 0, 001 ; INS1: r = 0, 194, p = 0, 003 ; INS2: r = 0, 022, p = 0, 001 ), testosterone (r = 0, 130, p = 0, 046 ), androstenedione (r = 0, 212, p = 0, 001 ), and DHEAS (r = 0, 178, p = 0, 006 ) and negatively correlated with progesterone (r = − 0, 204, p = 0, 002 ), estradiol (r = − 0, 140, p = 0, 032 ), and SHBG (r = − 0, 308, p < 0, 001 ). CRP positively correlated with insulin concentration in 0, 60, and 120 min during the oral glucose tolerance test (INS0: r = 0, 343, p < 0, 001 ; INS1: r = 0, 276, p = 0, 001 ; INS2: r = 0, 320, p < 001 ) and negatively correlated with progesterone (r = − 0, 194, p = 0, 030 ) and SHBG (-0, 244, p = 0, 005 ). We also estimated positive correlation between BMI and serum CRP and WBC concentration. Multiple linear regression analysis showed that CRP values are positively associated with BMI (beta = 0, 374, p < 0, 001 ) and insulin level (INS1) (beta = 0, 282, p = 0, 004 ); and WBC results are negatively associated with SHGB (beta = − 0, 284, p < 0, 001 ) but positively associated with testosterone (beta = 0, 163, p = 0, 024 ) and BMI (beta = 0, 157, p = 0, 047 ). PCOS is associated with increased WBC and CRP concentrations. The main predicting factors of increased CRP are BMI and insulin resistance, but there is also a relationship between WBC count in PCOS and androgen concentration itself so that inflammation may be mediated not only through adiposity but also through increased androgen concentration.